2016
DOI: 10.5399/osu/jtrf.55.2.4358
|View full text |Cite
|
Sign up to set email alerts
|

Local Sensitivity Analysis of Forecast Uncertainty in a Random-Utility-Based Multiregional Input-Output Model

Abstract: Transportation systems are critical to regional economies and quality of life. The Random-Utility-Based Multiregional Input-Output Model (RUBMRIO) for trade and travel choices is used here to appreciate the distributed nature of commodity flow patterns across the United States’ 3,109 contiguous counties and 12 industry sectors, for rail and truck operations. This paper demonstrates the model’s sensitivity to various inputs using the method of local sensitivity analysis with interactions (LSAI). This work simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Then, Borgonovo et al ( 21 ) used the G-LUM by Kockelman ( 15 ) to illustrate LSAI techniques and found that the outputs respond almost additively to variations in model inputs over the given scenarios. Wang and Kockelman ( 22 ) applied LSAI to evaluate random–utility-based multiregional input-output models by producing FCSI for the variation of inputs under different scenarios.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Then, Borgonovo et al ( 21 ) used the G-LUM by Kockelman ( 15 ) to illustrate LSAI techniques and found that the outputs respond almost additively to variations in model inputs over the given scenarios. Wang and Kockelman ( 22 ) applied LSAI to evaluate random–utility-based multiregional input-output models by producing FCSI for the variation of inputs under different scenarios.…”
Section: Literature Reviewmentioning
confidence: 99%